Appendix to How Developers and Managers Define and Trade Off Productivity and Quality - Storey, Margaret-Anne; Houck, Brian; Zimmermann, Tom (Microsoft, 2021)
This technical report includes two Microsoft Research surveys that were deployed to software engineers and software engineering managers to learn about their definitions and alignment with respect to software productivity and quality.